2020
DOI: 10.1111/echo.14947
|View full text |Cite
|
Sign up to set email alerts
|

Double left brachiocephalic veins with vascular ring and normal intracardiac anatomy: Prenatal diagnosis of a rare association

Abstract: One of the extremely rare systemic venous anomalies is double left brachiocephalic veins (LBVs). In the current work, a rare association of double LBVs with a vascular ring and normal intracardiac anatomy is described in fetal life with postnatal confirmation using echocardiography and computed tomography. The prenatal diagnosis of such an infrequent lesion is feasible using fetal echocardiography. Despite the smooth prenatal and postnatal course, potential risk during certain interventions or surgeries should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The mean maternal age at diagnosis was 30.2 years, and the mean gestational age at diagnosis was 23.4 weeks. Fetal echocardiography was the diagnostic method of LBCV anomalies in 15 studies [ 7 , 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and in our series, while fetal magnetic resonance was used in one study [ 27 ]. In studies in which the initial sample was reported, LBVCA appeared to have an incidence from 0.02% to 6.5% [ 7 , 16 , 18 , 23 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mean maternal age at diagnosis was 30.2 years, and the mean gestational age at diagnosis was 23.4 weeks. Fetal echocardiography was the diagnostic method of LBCV anomalies in 15 studies [ 7 , 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and in our series, while fetal magnetic resonance was used in one study [ 27 ]. In studies in which the initial sample was reported, LBVCA appeared to have an incidence from 0.02% to 6.5% [ 7 , 16 , 18 , 23 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although anomalous LBCV courses are very rare before delivery, they have been reported given the widespread use of fetal echocardiography [4][5][6][7][8][9]. The 3VT view is the most important view for the diagnosis of anomalous LBCV courses because the 3VT view can show fetal blood vessels, cardiac vessels, and the thymus [3,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, a circum-aortic or double LBCV is exceedingly unusual, making up only 0.7% of all anomalous LBCV cases [2] . LBCV anatomic abnormalities can occur in association with other congenital cardiac defects, most commonly tetralogy of Fallot [3] . Notably, no other cardiac structural abnormalities were observed in this case of anomalous LBCV.…”
Section: Discussionmentioning
confidence: 99%
“…Prior retrospective studies on demographic characteristics of LBCV cases demonstrated a mean age of diagnosis of 4 years and 9 months with a male predominance of 1.5:1, but these studies are limited by sample size due to the rarity of this anomaly [1 , 4] . Risk factors for anomalous development of the LBCV are unknown, but are possibly similar to those associated with other congenital cardiac malformations, such as uncontrolled maternal diabetes, intrauterine alcohol or tobacco exposure, or chromosomal abnormalities [3] .…”
Section: Discussionmentioning
confidence: 99%